Patient reactions to community pharmacies' roles: evidence from the Portuguese market - Nunes, F. G. (2016)
Background: There is little knowledge about how patients perceive and react to the extended role of community pharmacies. Aim: To develop a model describing the expanded role of Portuguese community pharmacies as comprising three roles - medicines supplier, advice provider and community health promoter - and two important patient reactions: satisfaction and loyalty. Design: In 2010, 1200 face-to-face interviews were conducted with patients of community pharmacies in Portugal. A model comprising the three pharmacy roles and the two patient reactions was developed and tested using structural equation modelling. Results: The results showed that the model was appropriate and that the roles of medicines supplier, advice provider and community health promoter were positively related to patients' satisfaction and loyalty. Conclusions: These results show that patients are aware of the different roles played by community pharmacies in Portugal. The data support the idea that the movement of Portuguese pharmacists' extended role, framed within a global context where society sends expectations regarding the role of organizations in the community in which they operate, is producing positive results for both patients and pharmacists.